Prediksi Pemilihan Fakultas Di Universitas Pada Sekolah Menengah Atas Negeri XXX Tangerang Selatan Dengan Menggunakan Algoritma C4.5 - Chrisantus Tristianto; Afrizal Zein (Institut Sains dan Teknologi Nasional, 2022)
Abstract This research was made to determine and find out the selection of faculties/departments that students will choose after they graduate. The data studied were 203 student data consisting of 169 students majoring in Science, while for Social Sciences majors there were 34 students. The method used in this research is to use the C4.5 algorithm method which can manage input values ​​based on UN scores (national exams) for certain subjects. This standard can be measured quantitatively using the C4.5 data mining algorithm method. The application is designed to be able to analyze the grades students receive after graduation. From the existing problems, a classification method is tested by applying a decision tree model, namely using the C4.5 method. After testing, the results obtained were that when running the decision tree algorithm, the accuracy of the C4.5 prediction obtained the highest accuracy of 77.16%. Keywords: Analysis, C4.5 Algorithm, Faculty Selection, Prediction